2017
DOI: 10.2147/opth.s118689
|View full text |Cite
|
Sign up to set email alerts
|

Patient considerations in ocular hypertension: role of bimatoprost ophthalmic solution

Abstract: Glaucoma is a leading cause of irreversible blindness worldwide. The reduction of intraocular pressure has been well established as an effective treatment to prevent both the development and the progression of all forms of glaucoma. Bimatoprost 0.03% ophthalmic solution, introduced in 2001, is a synthetic prostamide with the unique mechanism of improving both uveoscleral and trabecular outflow. Comparative studies with other pharmacotherapies have shown favorable results for bimatoprost as a potent ocular hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…The four FP‐PGAs approved for use in the United States, the EU and Japan as of late 2017 are latanoprost (Digiuni et al, ), travoprost (Quaranta et al, ), bimatoprost (Lee et al, ) and tafluprost (Keating, ) (Figure ). These are widely thought to be prodrugs, with their biomolecular mechanism of action believed to be activation of the PG FP receptor by their derivative, free carboxylic acid moiety.…”
Section: The Clinical Utility Of Pg Analoguesmentioning
confidence: 99%
“…The four FP‐PGAs approved for use in the United States, the EU and Japan as of late 2017 are latanoprost (Digiuni et al, ), travoprost (Quaranta et al, ), bimatoprost (Lee et al, ) and tafluprost (Keating, ) (Figure ). These are widely thought to be prodrugs, with their biomolecular mechanism of action believed to be activation of the PG FP receptor by their derivative, free carboxylic acid moiety.…”
Section: The Clinical Utility Of Pg Analoguesmentioning
confidence: 99%
“…It was reported that bimatoprost induced skin pigmentation and iris pigmentation as adverse effects . Periocular pigmentation has been reported to occur more frequently with bimatoprost than with other prostaglandins . Moreover, periocular pigmentation occurs more frequently in Asians than in Caucasians .…”
Section: Introductionmentioning
confidence: 99%
“…Mediation of a prostaglandin‐induced upregulation of tyrosinase is thought to be a possible mechanism of iris pigmentation caused by bimatoprost . In one small study, bimatoprost was used to treat facial and non‐facial vitiligo with moderate success, although larger and long‐term trials are pending …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations